2023
DOI: 10.3390/ijms241813719
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gene Expression in the Retina, Optic Nerve Head, and Optic Nerve of Mice with Optic Nerve Crush and Experimental Glaucoma

Casey J. Keuthan,
Julie A. Schaub,
Meihan Wei
et al.

Abstract: A major risk factor for glaucomatous optic neuropathy is the level of intraocular pressure (IOP), which can lead to retinal ganglion cell axon injury and cell death. The optic nerve has a rostral unmyelinated portion at the optic nerve head followed by a caudal myelinated region. The unmyelinated region is differentially susceptible to IOP-induced damage in rodent models and human glaucoma. While several studies have analyzed gene expression changes in the mouse optic nerve following optic nerve injury, few we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“… 13 In contrast, morphologic analysis of the LC of early glaucoma monkey eyes reported both thinning and thickening of the connective tissue beams, where areas with thinner beams had greater pore diameters, and areas with thicker beams had smaller pore diameters. 64 We are presently comparing the differential gene expression between healthy, crush injury, and glaucoma mouse models 65 to help explain the differences in the ex vivo biomechanical strain behavior found in this study and the differences in the microanatomy found elsewhere.…”
Section: Discussionmentioning
confidence: 85%
“… 13 In contrast, morphologic analysis of the LC of early glaucoma monkey eyes reported both thinning and thickening of the connective tissue beams, where areas with thinner beams had greater pore diameters, and areas with thicker beams had smaller pore diameters. 64 We are presently comparing the differential gene expression between healthy, crush injury, and glaucoma mouse models 65 to help explain the differences in the ex vivo biomechanical strain behavior found in this study and the differences in the microanatomy found elsewhere.…”
Section: Discussionmentioning
confidence: 85%
“…Studies have shown that nerve growth factor (NGF) promotes the formation of lamentous pseudopods and branches of axons through the PI3K-Akt signaling pathway [39] . The PI3K-Akt signaling pathway has been shown to be associated with ND [40][41][42] . Considering the regulatory effect of the PI3K-Akt signaling pathway and key targets such as TP53, PI3KCA, PIK3R1, RTK2, and GRB2 on nerve injury and combined with the ndings of previous studies, acrylamide was found to regulate the PI3K-Akt signaling pathway [43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IOP in rodent models produces optic neuropathology that was first observed in the unmyelinated portion of the optic nerve head, an area that corresponds to the lesion in human glaucoma 93 . Gene expression patterns in the unmyelinated optic nerve showed significant enrichment in the Hippo pathway compared to that in the myelinated optic nerve and retina 94 . The role of the Hippo signalling pathway in glaucoma is mainly reflected in the regulation of cell fibrosis and optic nerve protection.…”
Section: Hippo Signalling Pathway In Eye Diseasesmentioning
confidence: 97%
“…93 Gene expression patterns in the unmyelinated optic nerve showed significant enrichment in the Hippo pathway compared to that in the myelinated optic nerve and retina. 94 The role of the Hippo signalling pathway in glaucoma is mainly reflected in the regulation of cell fibrosis and optic nerve protection.…”
Section: Glaucomamentioning
confidence: 99%